A PPAR gamma agonist protects against oral mucositis induced by irradiation in a murine model. (January 2017) - Mangoni, Monica; Sottili, Mariangela; Gerini, Chiara; Desideri, Isacco; Bastida, Cinzia; Pallotta, Stefania; Castiglione, Francesca; Bonomo, Pierluigi; Meattini, Icro; Greto, Daniela; Olmetto, Emanuela; Terziani, Francesca; et al.
Highlights: Oral mucositis is a complication of radiotherapy used for head-neck cancer treatment. Rosiglitazone protects normal tissues from radiation-induced oral mucositis. Rosiglitazone does not protect the tumor from therapeutic effect of irradiation. Rosiglitazone could be proposed as radioprotective agent in head-neck cancer. Abstract: Background: Due to its anti-inflammatory, antifibrotic and antineoplastic properties, the PPAR gamma agonist rosiglitazone is of interest in prevention and therapy of radiation-induced toxicities. We aimed to evaluate the radioprotective effect of rosiglitazone in a mouse model of radiation-induced oral mucositis. Material and methods: Oral mucositis was obtained by irradiation of the oral region of C57BL/6J mice, pretreated or not with rosiglitazone. Mucositis was assessed by macroscopic scoring, histology and molecular analysis. Tumor xenograft was obtained by s.c. injection of Hep-2 cells in CD1 mice. Tumor volume was measured twice a week to evaluate effect of rosiglitazone alone and combined with radiotherapy. Results: Irradiated mice showed typical features of oral mucositis, such as oedema and reddening, reaching the peak of damage after 12–15 days. Rosiglitazone markedly reduced visible signs of mucositis and significantly reduced the peak. Histological analysis showed the presence of an inflammatory cell infiltrate after irradiation; the association with rosiglitazone noticeably reduced infiltration. Rosiglitazone significantly inhibited radiation-induced tnf α, Il- 6 and Il-1 β gene expression. Rosiglitazone controlled the increase of TGF-β and NF-kB p65 subunit proteins induced by irradiation, and enhanced the expression of catalase. Irradiation and rosiglitazone significantly reduced tumor volume as compared to control. Rosiglitazone did not protect tumor from the therapeutic effect of radiation. Conclusion: Rosiglitazone exerted a protective action on normal tissues in radiation-induced mucositis. Moreover, it showed antineoplastic properties on head-neck carcinoma xenograft model and selective protection of normal tissues. Thus, PPAR gamma agonists should be further investigated as radioprotective agents in head and neck cancer.